Scientific Approach to Teach English Vocabulary For Mentally Retarded Students - Sholeh, Agus; Ayu, Shofi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. For mentally retarded children, a structured and careful teaching method is needed to facilitate students’ understanding of learning English vocabulary. This study aims to: (1). Describe the application of a scientific approach to English vocabulary subjects; (2). Describe the obstacles to applying a scientific approach to learning English vocabulary for mentally retarded children; (3). Describe the benefits of applying a scientific approach to learning English vocabulary for mentally retarded children. The research method used is descriptive qualitative. The subject in this study was 3 teachers with 5 students for each of class VII of State Special Needs Junior High School Pembina . Data collection techniques used are observation techniques, interviews, and documentation. Data analysis is done by organizing the data, breaking it down into units, synthesizing it, arranging it into a pattern, choosing what is important and what  be studied, and making conclusions that can be told to others. The results shows that many benefits for both teachers and students, especially for mentally retarded students, including improving students' thinking skills, making it easier for students to understand the learning materials taught by teachers, and being more meaningful for students and this approach has obstacles and shortcomings when applied to mentally retarded children in a different class and should be simplified and adapted to the abilities of these students. The findings of this study highlight the importance of adapting teaching methods to better meet the needs of mentally retarded children, which can lead to more inclusive and effective educational practices. Socially, the research emphasizes the value of equal educational opportunities, contributing to a more inclusive and supportive learning environment for all studentsKeywords: Mentally Retarded, Scientific Approach English Vocabulary